Analisis Metafora dalam Lirik Lagu Satu Tuju dan Kau Rumahku Karya Raissa Anggiani - Azzahra, Aulia; Faarisah, Shabrina; Nurjanah, Neneng (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The purpose of this study is to describe the metaphors found in the lyrics of the song "Satu Tuju dan Kau Rumahku" by Raissa Anggiani. This data collection technique uses observing and note-taking techniques. Analysis of the data used in this study using descriptive analysis in the form of descriptions using informal techniques in the form of descriptions. The theory used in this study is to use metaphor theory according to Lakoff and Johnson. The results of this study show that in the song "Satu Tuju", the writer gets the results in the form of 6 ontological metaphors and 5 structuralist metaphors, while in the song "Kau Rumahku" there are 3 ontological metaphors, 2 orientational metaphors, and 1 structural metaphor. So it can be said that Raissa Anggiani's songs generally use a lot of ontological metaphors to show her turmoil. The metaphors contained in Raissa Anggiani's song lyrics make use of ontological metaphors which analogize a person's heart or feelings with animals and natural events around them with the intention of expressing feelings and showing their turmoil.